ChemInform Abstract: Ca3Na4LiBe4B10O24F: A New Beryllium Borate with a Unique Beryl Borate ∞2 [Be8B16O40F2] Layer Intrabridged by [B12O24] Groups. Issue 42 (14th October 2014) - Luo, Siyang; Yao, Wenjiao; Gong, Pifu; Yao, Jiyong; Lin, Zheshuai; Chen, Chuangtian
Abstract Single crystals of the new title compound are prepared by melting mixtures of Na2CO3, CaCO3, LiF, BeO, and B2O3 with a molar ratio of 0.9:0.5:0.4:1:2 (Pt crucible, 900 °C).